Soil health: looking for suitable indicators. What should be considered to assess the effects of use and management on soil health? (Scientia Agricola, 2013)
Soil Health refers to the ecological equilibrium and the functionality of a soil and its capacity to maintain a well balanced ecosystem with high biodiversity above and below surface, and productivity. To understand and use soil health as a tool for sustainability, physical, chemical, and biological properties must be employed to verify which respond to the soil use and management within a desired timescale. Attributes with a rapid response to natural or anthropogenic actions are considered good indicators of soil health. Among the physical indicators, soil texture, aggregation, moisture, porosity, and bulk density have been used, while among chemical indicators total C and N, mineral nutrients, organic matter, cation exchange capacity, among others are well established. However, most of them generally have a slow response, when compared to the biological ones, such as microbial biomass C and N, biodiversity, soil enzymes, soil respiration, etc., in addition to macro and mesofauna. Thus, a systemic approach based on different kinds of indicators (physical, chemical and biological) in assessing soil health would be safer than using only one kind of attribute. Many human activities have caused desertification, loss of biodiversity, disruption of aggregates, loss of organic matter and nutrients, among others. Today, it is imperious to maintain soil health and productivity with increasing emphasis on reforestation and recuperation of degraded areas through the use of organic amendments, reintroduction of plants, soil fauna and microorganisms. This review focused on an integrative view on indicators of soil health to be used as tools for prediction of sustainability in production systems.